FINANCIAL HEALTH ASSESSMENT OF PT. PLN (PERSERO) 2019-2022: TOWARDS FINANCIAL SUSTAINABILITY - Regita Vyonda; Sanda Patrisia Komalasari (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This research aims to measure the financial performance of PT. PLN (Persero) in 2019-2022 uses financial ratios in accordance with the regulations of the Ministry of State-owned enterprises (BUMN). The sample for this research is PT PLN (Persero) financial report for four years. The research method used is a case study with an analysis of liquidity, solvency, activity and profitability ratios. The analysis was carried out based on the Decree of the Minister of BUMN No. KEP-100/MBU/2002. The research results show that the liquidity ratio of PT. PLN (Persero) was 95.02%, 64.98%, 58.63% and 82.30%, respectively. The solvency ratio shows debt to assets of 41.37%, 40.85%, 39.15% and 39.48%. Profitability ratios show ROEs of 0.47%, 0.64%, 1.34% and 1.45%. Based on this analysis, PT. PLN (Persero) was categorized as "Less Healthy" during that period. In conclusion, despite some stable financial indicators, several aspects require further attention to ensure continued positive performance. Companies are advised to improve operational efficiency and debt management to strengthen their overall financial position.